若丨a+1丨+(b-2)^2=0,求(a+b)^2011+a^2010的值.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 22:00:30
若丨a+1丨+(b-2)^2=0,求(a+b)^2011+a^2010的值.若丨a+1丨+(b-2)^2=0,求(a+b)^2011+a^2010的值.若丨a+1丨+(b-2)^2=0,求(a+b)^
若丨a+1丨+(b-2)^2=0,求(a+b)^2011+a^2010的值.
若丨a+1丨+(b-2)^2=0,求(a+b)^2011+a^2010的值.
若丨a+1丨+(b-2)^2=0,求(a+b)^2011+a^2010的值.
丨a+1丨+(b-2)^2=0
a=-1 b=2
(a+b)^2011+a^2010
=(-1+2)^2011+(-1)^2010
=1+1
=2
丨a+1丨+(b-2)^2=0,
所以
a+1=0
b-2=0
a=-1
b=2
(a+b)^2011+a^2010
=(-1+2)^2011+(-1)^2010
=1+1
=2
丨a+1丨+(b-2)^2=0
∴a+1=0
b-2=0
∴a=-1
b=2
∴(a+b)^2011+a^2010
=(-1+2)^2011+(-1)^2010
=1+1
=2
2